Konsep Pesantren dalam Menanamkan Akhlak Santri terhadap Guru di Pondok Pesantren al-Falah Bahrul Ulum Tambakberas Jombang - Ahmad Jauharul Insan; Wahyudi Wahyudi (Lembaga Yasin AlSys, 2026)
Although character education in Islamic boarding schools has received attention in various previous studies, research that specifically discusses the philosophical concepts and implementation strategies for cultivating students’ morals toward teachers in traditional pesantren remains limited. This study aims to analyze the pesantren concept in cultivating students’ morals toward teachers, examine its implementation in daily life, and identify its supporting and inhibiting factors at Pondok Pesantren Al-Falah Bahrul Ulum Tambakberas Jombang. This study used a descriptive qualitative approach with a case study design. Data were collected through participatory observation, in-depth interviews with the kyai, mentors, pesantren administrators, and students, as well as document analysis. The results show that the core concept of cultivating students’ morals toward teachers rests on the values of ta’dzim or respect, tawadhu’ or humility, and khidmah or service. These values are not taught as separate subjects but are integrated into all students’ daily activities, such as congregational prayers, Qur’anic study, and direct interaction with teachers. These findings broaden the understanding of hidden curriculum practices in the salafiyyah pesantren tradition and contribute to the development of Islamic character education literature. The conclusion of this study affirms that the commitment of the kyai and the exemplary conduct of mentors are the main supporting factors, while the influence of social media technology and the adolescent developmental phase are inhibiting factors that need to be anticipated through restrictions on gadget use and the strengthening of pesantren supervision. The implications of this study include providing a model of moral education based on classical Islamic tradition that can be adapted by other Islamic educational institutions and opening opportunities for comparative research across types of pesantren in the digital era.